A linguagem do videogame como ferramenta auxiliar no processo de ensino e aprendizado - Goya, Julia Yuri Landim [UNESP]; Rossi, Dorival Campos [UNESP] (My University, 2014)
Thisarticlediscussesissuesrelatedtothedesignlang uagewith a focusonteachingandlearningthroughthe useofgamesas a tool touncoverthe world. The gamesare abletosystematizethelanguagesothatyoucanlearnbyplayingthi swayandmakingthe interfacemore playful, more accessibleandlike us. Playing as apusherelementof newpossibilitiesandgamesare emergingas aplayfulargumentfor teachingin theman-machine interface.
Keywords: Game Design; Learning; Teaching; Videogames